Resilience during uncertainty? Greater social connectedness during COVID‐19 lockdown is associated with reduced distress and fatigue. Issue 2 (25th October 2020) - Nitschke, Jonas P.; Forbes, Paul A. G.; Ali, Nida; Cutler, Jo; Apps, Matthew A. J.; Lockwood, Patricia L.; Lamm, Claus
Abstract : Background: Social connections are crucial for our health and well‐being. This is especially true during times of high uncertainty and distress, such as during the COVID‐19 lockdown. This period was characterized by unprecedented physical distancing (often communicated as social distancing) measures resulting in significant changes to people's usual social lives. Given the potential effects of this disruption on people's well‐being, it is crucial to identify factors which are associated with negative health outcomes, and conversely, those that promote resilience during times of adversity. Aims: We examined the relationship between individuals' levels of social connectedness during lockdown and self‐reported stress, worry, and fatigue. Method: Survey data were collected from 981 individuals in a representative sample of Austrian citizens. Data collection occurred during the last week of a six‐week nationwide lockdown due to the COVID‐19 pandemic. The final sample consisted of 902 participants. Participants were asked to complete validated questionnaires to assess levels of social connectedness as well as measures of perceived stress, worry—both general and COVID‐19 specific—and symptoms of fatigue during the previous two weeks. Results: Our results demonstrate that greater social connectedness during the lockdown period was associated with lower levels of perceived stress, as well as general and COVID‐19‐specific worries. Furthermore, we found a negative relationship between fatigue and social connectedness, which was mediated by feelings of stress, general worries, and COVID‐19‐specific worries—respectively, indicating that individuals with smaller network sizes, who were highly distressed during the pandemic, were also likely to report feeling more fatigued. Conclusion: Our findings highlight the important role that social connections play in promoting resilience by buffering against negative physical and mental health outcomes, particularly in times of adversity in times of adversity.